Material Designing: Peculiarities and Models - Abduraimova, Yayra (International Journal on Human-Computing Studies, 2023)
The article deals with the issues based on material designing as an effective tool for creating educational materials, including in the field of e-learning. The very concept of material design is analyzed in the historical aspect, its models and principles are presented. Designing materials allows instructors to investigate and acquire new information, which takes the form of assignments. Material design, in the framework of preparing students for corporate work life, not only exposes students to diverse learning circumstances, but also assists teachers in developing their professional abilities.